A chemically contiguous hapten approach for a heroin–fentanyl vaccine - Natori, Yoshihiro; Hwang, Candy S.; Lin, Lucy; Smith, Lauren C.; Zhou, Bin; Janda, Kim D. (Beilstein Journal of Organic Chemistry, 2019)
Background: Increased death due to the opioid epidemic in the United States has necessitated the development of new strategies to treat addiction. Monoclonal antibodies and antidrug vaccines provide a tool that both aids addiction management and reduces the potential for overdose. Dual drug vaccines formulated by successive conjugation or by mixture have certain drawbacks. The current study examines an approach for combatting the dangers of fentanyl-laced heroin, by using a hapten with one epitope that has domains for both fentanyl and heroin.Results: We evaluated a series of nine vaccines developed from chemically contiguous haptens composed of both heroin- and fentanyl-like domains. Analysis of the results obtained by SPR and ELISA revealed trends in antibody affinity and titers for heroin and fentanyl based on epitope size and linker location. In antinociception studies, the best performing vaccines offered comparable protection against heroin as our benchmark heroin vaccine, but exhibited attenuated protection against fentanyl compared to our fentanyl vaccine.Conclusion: After thorough investigation of this strategy, we have identified key considerations for the development of a chemically contiguous heroin–fentanyl vaccine. Importantly, this is the first report of such a strategy in the opioid–drug–vaccine field.
Keywords: antinociception; fentanyl; hapten; heroin; vaccine